From tangible to intangible heritage: Hollókő, the “world-protected village” - Sonkoly, Gábor (Ethnologies, 2019)
Hollóko, the first World Heritage village in Europe (since 1987), is exemplary not only because its long history of preservation ranges over different cultural heritage regimes and integrates various levels of heritage protection, but also because it is a village which incorporates intangible heritage elements from the beginning of its conservation in spite of the fact that first it is only protected as an ensemble of vernacular buildings. The article shows by the analysis of the sixty plus years of the documented heritage protection of this village how the regimes of cultural heritage unfold; how cultural heritage agency functions in the context of the interactions between locals, professionals and visitors; and how this heritage village embodies different levels of cultural heritage. The cultural heritage agency is examined in a matrix, which is determined by the three regimes of cultural heritage and by the multiple levels of heritage interpretations ranging from universal to local. The heritagization of the village proves that this process does not wipe out, but reuses broken social practices and that the locals form a public community for which the rather sharp line separating public and private spheres is blurred and needs to be managed.